2017
DOI: 10.5897/ajmm2015.0454
|View full text |Cite
|
Sign up to set email alerts
|

Marketing practices and challenges of Mung Bean in Ethiopia Amhara Regional State: North Shewa Zone in focus

Abstract: Mung beans are grown widely for use as a human food (as dry beans or fresh sprouts), but can be used as a green manure crop and as forage for livestock. This study assessed the marketing practice and challenges of Mung bean in the Amhara Region, North Shewa Zone. Descriptive analysis techniques were used for conducting this research. From the nine selected districts, 1,350 producers, 115 traders and 10 experts/professionals were taken as a sample using convenience sampling techniques. The interviewer administe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Similarly, mung bean is highly preferred to sesame due to its shorter growing period, low input requirement, and high market demand (Mohammed et al, 2017).…”
Section: Sustainability Of the Sesame Value Chaincontinuity Of Produc...mentioning
confidence: 99%
“…Similarly, mung bean is highly preferred to sesame due to its shorter growing period, low input requirement, and high market demand (Mohammed et al, 2017).…”
Section: Sustainability Of the Sesame Value Chaincontinuity Of Produc...mentioning
confidence: 99%
“…Hence, producer farmers were sold out the whole produce immediately after harvesting. Farmers sell 75 to 80% of their marketable surplus immediately after harvesting their product (Mohammed et al, 2017). However, it was observed that the market price during harvesting seasons was very low.…”
Section: Market Linkage and Sustainability Of The Technologymentioning
confidence: 99%
“…Farmers have also suffered from a lack of access to improved seed, low market price during harvesting and price fluctuation across traders and time, and postharvest loss due to weevils. Similarly, (Mohammed et al, 2017;Yehuala et al, 2018) mentioned the prevalence of pests and disease, lack of improved seed supply, lack of proper storage and handling, and inappropriate market chain (poor coordination among traders, extended market chain, lack of market information, price impulsiveness, lack of market promotion).…”
Section: Constraints Of Mung Bean Production During the Scaling Upmentioning
confidence: 99%
“…So, different theoretical literatures and practical works indicate having efficient domestic agricultural commodity marketing system plays a major role in accelerating the growth and development of the agriculture sector. Besides, it makes the participants in the market chain such as producers, traders and consumers' beneficiary as per their role and efforts exerted in the system (Mohammed, et, al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Undeveloped and unorganized marketing system have several economic problems, such as it may lead an inflationary and disinflationary environment, low return for producer, loss of foreign currency by exporting less of the commodity low capital formation and low investment of farmers. (Muhammed et al, 2015).…”
Section: Introductionmentioning
confidence: 99%